Magic and witchcraft: Implications for Democratization and poverty-alleviating aid in Africa - Dirk Kohnert (World Development, 1996)
The belief in occult forces is still deeply rooted in many African societies, regardless of education, religion, and social class of the people concerned. According to many Africans its incidence is even increasing due to social stress and strain caused (among others) by the process of modernization. Most often magic and witchcraft accusations work to the disadvantage of the poor and deprived, but under particular circumstances they become a means of the poor in the struggle against oppression by establishing “cults of counterviolence”. Magic and witchcraft beliefs have increasingly been instrumentalized for political purposes. Apparently they can be used to support any kind of political system, whether despotic or democratic. The belief in occult forces has serious implications for development cooperation. Development projects, which constitute arenas of strategic groups in their struggle for power and control over project resources, are likely to add further social stress to an already endangered precarious balance of power, causing witchcraft accusations to flourish. In addition, witchcraft accusations may serve as indicators of hidden social conflicts which are difficult to detect by other methods. – – Magie et la sorcellerie: Implications pour la démocratisation et l'aide pour la réduction de la pauvreté en Afrique: La croyance dans les forces occultes est encore profondément enracinée dans de nombreuses sociétés africaines, indépendamment de l'éducation, de la religion, et la classe sociale des personnes concernées. Selon de nombreux Africains son incidence est encore agrandissant à cause d'un stress sociale croissant et tension causée (entre autres) par le processus de modernisation. Le plus souvent des accusations de la sorcellerie travaillent sous ces conditions au détriment des pauvres et des misérables. Mais dans des circonstances particulières ils deviennent des moyens des pauvres dans la lutte contre l'oppression en développant de «cultes de contre violence". Occulte croyances africaines, comme magie et sorcellerie, ont été instrumentalisée à des fins politiques. Apparemment, ils peuvent être utilisés pour soutenir tout type de système politique, soit despotique ou démocratique. La croyance dans les forces occultes à de graves conséquences pour la coopération au développement. Les projets de développement, qui constituent des arènes de groupes stratégiques dans leur lutte pour le pouvoir et le contrôle sur les ressources du projet, sont susceptibles d'ajouter un stress supplémentaire à l'équilibre précaire de la puissance au niveau local, causant des accusations de sorcellerie à augmenter. En outre, des accusations de sorcellerie peuvent servir comme indicateurs de conflits sociaux cachés qui sont difficiles à détecter par d'autres méthodes.
Additional information: Author's version
Keywords: N3; N37; N97; O17; O2; O55; Z12; Z13; 330; Occult belief systems; Africa; Development aid; poverty alleviation; democratization; Entwicklungsforschung; Subsahara-Afrika; Religion; Volksglaube; Demokratie; Armutsbekämpfung